Pengaruh Strategi Quantum Learning Terhadap Hasil Belajar Menulis Teks Tanggapan Deskriptif - Citra Indraswari; Kurnia Kurnia; Suhaebah Nur (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Al Asyariah Mandar, 2018)
In the implementation of the learning ability to write descriptive response text. lack of use of a variety of strategies causes students to feel bored following learning. The reality happened to students of class VII A as an experimental (group) class, and class VII B as a class (group) control of 5 Wonomulyo State Junior High School in Polewali Mandar District. The population of this study was the entire class VII of the 5th Junior High School of Wonomulyo, Polewali Mandar Regency, totaling 176 people, who were placed in five classes. The sample in this study were 2 classes randomly selected from 6 classes based on the results of simple random sampling and prior to determining the sample beforehand the initial test (Pre-test) was carried out to all participants in class VII of the 5 Wonomulyo Junior High School and the class that obtained grades the same or almost the same average is taken as an assessment class. This assessment will use 1 experimental class and 1 control class. Based on the results of simple random sampling, class VII A as an experimental class, and class VII B as a control class. The data analysis technique used is descriptive statistical analysis and inferential statistical analysis. The inferential statistical test results show that the value of t count at equal variances assumed = 2.034 df = 54, and obtained t table = 2.004 so that t count = 2.034> t table = 2.004 and significance 0.004